Understanding the effects of mineralogy, ore texture and microwave power delivery on microwave treatment of ores. - Ali, Abubeker Yimam (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Process Engineering))--University of Stellenbosch, 2010.